Strategi Komunikasi Efektif Petugas Customer Service terhadap Peningkatan Pelayanan Penumpang pada PT Angkasa Pura I di Bandar Udara Internasional Zainnuddin Abdul Madjid Lombok - Akbar Ade Pratama; Rezty Fauziah Novianti (Pusat Riset dan Inovasi Nasional, 2024)
The problem that occurs to the customer service officer at the time of location is when the customer service officer handles passengers who come to ask for information related to the flight or a problem at the airport and so on. This research aims to find out how the effective kuminukasi strategy by customer service officers in improving service to passengers at PT. Angkasa Pura I at Zainuddin Abdul Madjid Lombok International Airport. This research was conducted in 2023 at Zainuddin Abdul Madjid Lombok International Airport using a qualitative method and the data collection was sourced from passengers experiencing communication problems. The next source comes from extracting data sources through online interviews with customer service officers about effective kuminukasi strategies for passengers, observations or direct observations on related objects. The results of research that has been carried out by researchers regarding how the effective form of communication of customer service officers in improving services to passengers related to flight information to passengers and others. In addition, there are also factors that can affect effective communication with passengers, namely knowledge, perception, emotional, and a Clear and Simple Language environment in terms of the use of easy-to-understand language and the avoidance of complex technical terms to ensure that all passengers can understand the information conveyed well.